From driver of change to marginalised actor: organised labour in post-revolutionary Egypt from a comparative perspective. Issue 6 (1st November 2020) - Abdalla, Nadine; Wolff, Jonas
ABSTRACT: The paper analyses why Egypt's labour movement, while having played a significant role in the run-up to the 2011 revolution, has been increasingly marginalised politically ever since, failing to achieve either significant labour-specific gains and/or broader objectives related to the overall process of political transformation. It does so by investigating Egypt's movement of independent trade unions, the most dynamic element within the country's labour movement, from a comparative perspective. Specifically, the paper uses the experience of Brazil's New Unionism in the 1980s as a contrasting case, identifies the factors that have enabled and constrained what is arguably the most successful example of a New Unionist movement in the Global South, and applies this explanatory framework in an in-depth study on the trajectory of Egypt's New Unionism since 2011. The study identifies four key differences between the Brazilian and the Egyptian case that help explain the post-revolutionary trajectory of independent labour in the latter: the different sequencing of neoliberal reforms and political liberalisation; the revolutionary character of the Egyptian uprising; the different role of individual movement entrepreneurs; and the lack of significant socio-political allies in the Egyptian case.